Birds Diversity Mapping using Quantum GIS For Ecotourism in The Mangrove Forest of Kuala Bubon, West Aceh - Ulhaq, Riza; Juliwardi, Ilham (AI Society & STMIK Indonesia, 2023)
The discourse on developing Kuala Bubon mangrove forest area in West Aceh as an ecotourism location has received a lot of sympathy and support among the community, considering that this forest has a high level of diversity of flora and fauna, one of which is bird species. In several ecotourism locations, birds attract tourists by enjoying various entertainment related to birds, such as bird watching, tours of bird habitats, and observing birds in the wild. The research was carried out in the Kuala Bubon mangrove forest, West Aceh, in September 2023. This research used a quantitative approach, calculating the level of diversity and mapping distribution based on bird location coordinates. The data collection method uses the point count and line transect method. Analysis of bird species diversity data using the Shannon-Wienner Diversity Index (H') formula was then carried out by mapping the coordinates of bird presence using the Quantum Gis software. The research results obtained 37 bird species from 22 families with a diversity index of 3.07 (high diversity), two species with the status of Near Threatened (Aegithina Viridissima) and Vulnerable Under (Acridotheres javanicus). Mapping bird species diversity with Quantum Gis provides opportunities for developing bird ecotourism, such as planning optimal bird-watching routes after knowing the distribution of bird species.